Study of the effect of adding (TiO2/MgO) on some mechanical and thermal properties of polyvinyl chloride (PVC) pipes exposed to sunlight (Damascus University Journal for engineering sciences, 2025)
In this research, the effect of adding (TiO2/MgO) to polyvinyl chloride (PVC) pipes exposed to sunlight was studied. Samples loaded with differentpercentages of these materials were manufactured and exposed to (UV) rays presented in sunlight that cause the decomposition of (PVC) material. By means of an aging device containing fluorescent tubes inside, and then conducting some mechanical and thermal tests (tensile and elongation, hardness, internal pressure, falling weights, longitudinal rebound (thermal effect), plasticizing point (Vicat softining)), where the results showed that samples containing ( TiO2/MgO) 2/2% showed the best mechanical properties Thus it is suitable for applications exposed to sunlight and heat up to 60 OC.
Keywords: Polyvinyl chloride (PVC) pipes; titanium dioxide (TiO2); Magnesium oxide (MgO); ultraviolet radiation (UV)